1975
DOI: 10.1128/aac.8.4.409
|View full text |Cite
|
Sign up to set email alerts
|

Unique Bactericidal Action of Metronidazole Against Bacteroides fragilis and Clostridium perfringens

Abstract: The comparative bactericidal activity of penicillin G, carbenicillin, clindamycin, and metronidazole against eight susceptible strains of Bacteroides fragilis and four strains of Clostridium perfringens was determined by performing colony counts anaerobically of cultures incubated in brucella broth. With the B. fragilis strains, there was a lag phase of growth of approximately 8 h, during which time metronidazole did not reduce the colony counts. However, within 4 h of the onset of exponential growth, metronid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
16
1
2

Year Published

1976
1976
1981
1981

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(20 citation statements)
references
References 16 publications
1
16
1
2
Order By: Relevance
“…This finding corroborates the discrepancy between in vitro and in vivo results noted in the lack of effectiveness of chloramphenicol in experimental B. fragilis abscesses in mice (35) (33). Despite a rapid in vitro bactericidal effect over 1 h or less (29) and serum levels comparable to those found in humans, metronidazole did not perform well in this experimental system.…”
Section: Resultscontrasting
confidence: 39%
“…This finding corroborates the discrepancy between in vitro and in vivo results noted in the lack of effectiveness of chloramphenicol in experimental B. fragilis abscesses in mice (35) (33). Despite a rapid in vitro bactericidal effect over 1 h or less (29) and serum levels comparable to those found in humans, metronidazole did not perform well in this experimental system.…”
Section: Resultscontrasting
confidence: 39%
“…On B. fragilis species, Clostridium species, and anaerobic gram-positive cocci its activity was poor. Tinidazole has a unique bactericidal action against B. fragilis and C. perfringens (10). In our studies, the drug appeared effective against all types of anaerobic microorganisms tested, with the exception of the anaerobic gram-positive cocci.…”
Section: Resultsmentioning
confidence: 63%
“…Ralph and Kirby suggested that metronidazole has a marked bactericidal effect which occurs after a prolonged lag phase (16). There remains the possibility, however, that this prolonged lag period was an artifact ofmethodology.…”
mentioning
confidence: 90%